SUMBER INSPIRASI PEMBENTUK KIAS DALAM PASAMBAHAN PADA UPACARA PERKAWINAN - nfn Arriyanti (Balai Bahasa Provinsi Riau, 2017)
This study discusses the source of inspiration in forming kias of pasambahan in the marriage ceremony in Luhak, district of Limapuluhkota. The Minangkabau have a variety of ideas sourced from their everyday lives to make kias in the pasambahan. Inspiration to make kias taken from various of flora, fauna, tools, and objects that are used in a variety of everyday activities. The sources of inspiration in forming Kias of pasambahan are classified and analyzed by using the qualitative method. Based on the analysis that was conducted on data, 10 the source of inspiration in forming kias of pasambahan are obtained, that is 1) kias by using plants, 2) kias by using animals, 3) kias by using food and drink, 4) kias by using activities, 5) kias by using natural events, 6) kias by using clothes and jewelry, 7) kias by using profession, 8) kias by using kitchen tools, 9) kias by using fishing equipment, and 10) kias by using the concept of religion.